Lithium metal deposition/dissolution under uniaxial pressure with high-rigidity layered polyethylene separator. Issue 30 (7th May 2020) - Kanamori, Shogo; Matsumoto, Mitsuhiro; Taminato, Sou; Mori, Daisuke; Takeda, Yasuo; Hah, Hoe Jin; Takeuchi, Takashi; Imanishi, Nobuyuki
Abstract : The use of a high rigidity separator and application of an appropriate amount of pressure are effective approaches to control lithium metal growth and improve its cycle performance. Abstract : The effects of mechanical uniaxial pressure and deflection of the separator on the electrochemical deposition of lithium metal were investigated. Instead of dendritic lithium growth without pressure, a much more dense and compact deposition can be achieved when pressure is applied to the cells during the lithium deposition process. This morphology is due to the formation of granular lithium followed by the generation of new lithium nuclei on the cathode surface. The improved lithium plating/stripping behavior in the cells under mechanical pressure yielded a 10% higher coulombic efficiency than cells without pressure. However, the cycle life is shortened with pressures higher than 1.39 MPa; therefore, there is an upper limit for improvement of the electrochemical characteristics near 1.39 MPa. The morphology of electrodeposited lithium becomes flatter with a large amount of electrodeposition under pressure when the number of polyethylene separators is increased to five due to the increase in the stiffness of the layered separators. Furthermore, high coulombic efficiency cycling by pressurization was increased to twice that for one separator sheet. Application of the optimal strength pressure and use of more inflexible separators are thus effective methods to control the microscopic morphology of electrodeposited lithium and improve the cycle performance of the lithium metal anode.